2012
DOI: 10.2166/wst.2012.338
|View full text |Cite
|
Sign up to set email alerts
|

Modeling mineral phase change chemistry of groundwater in a rural-urban fringe

Abstract: This research paper aims to determine the genetic origin of the chemical elements in groundwater. It deals with the results of physicochemical parameters, to evaluate the hydro-geochemistry of groundwater in rural-urban fringe of district Bareilly, India. Pre- and post-monsoon sampling has been carried out, which reveals inter-seasonal variability effect on the hydro-geochemical processes. Geochemical modeling especially computation of saturation index was undertaken using the WATEQ4F model. Majority of sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…The limitation of groundwater resource and aquifers (Singhal et al 1988) and longterm sustainability (Foster, et al 2002) is also a major issue. Many researchers have assessed groundwater quality in various parts of India (Prasad, 1998;Kaul, et al 1999;Abbasi, et al 2002;Jagdap, et al 2002;Gupta and Deshpande, 2004;Khaiwal and Garg, 2006;Prakash and Somashekar, 2006;Singh and Chandel, 2006;Shivran, et al 2006;Bishnoi and Arora, 2007;Gupta, et al 2008;Srinivasamoorthy, et al 2011;Singh, et al 2009;Singh, et al 2012;Singh, et al 2013aSingh, et al , 2013bSingh, et al , 2015Kumar, et al 2014). Chourasia and Tellam (1992) have reported that groundwater of irrigated areas have higher ionic concentration as compared to non-irrigated areas in hard rock terrain of central India.…”
Section: Introductionmentioning
confidence: 99%
“…The limitation of groundwater resource and aquifers (Singhal et al 1988) and longterm sustainability (Foster, et al 2002) is also a major issue. Many researchers have assessed groundwater quality in various parts of India (Prasad, 1998;Kaul, et al 1999;Abbasi, et al 2002;Jagdap, et al 2002;Gupta and Deshpande, 2004;Khaiwal and Garg, 2006;Prakash and Somashekar, 2006;Singh and Chandel, 2006;Shivran, et al 2006;Bishnoi and Arora, 2007;Gupta, et al 2008;Srinivasamoorthy, et al 2011;Singh, et al 2009;Singh, et al 2012;Singh, et al 2013aSingh, et al , 2013bSingh, et al , 2015Kumar, et al 2014). Chourasia and Tellam (1992) have reported that groundwater of irrigated areas have higher ionic concentration as compared to non-irrigated areas in hard rock terrain of central India.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to simplify surface and groundwater quality to a specific index because of its sensitive nature to inputs received from sources such as geogenic contribution, water-rock reactions, agricultural runoff, domestic, and industrial wastes (Singh et al 2012). However, the WQI by (Tiwari and Mishra 1985) and synthetic pollution index (SPI) (Ma et al 2009) are very useful and efficient methods for assessing the quality of water and presently used by many scientists and water managers.…”
Section: Water Quality Indices Estimationmentioning
confidence: 99%
“…On the other hand, geographic information system (GIS) is an important tool for spatial analysis and integration of spatial and nonspatial data to derive useful outputs (Singh et al 2013a;Patel et al 2011). It can be used for formulating a simple and robust water quality pollution assessment tool for rapid information generation and broadcasting to water resources managers and the public (Singh et al 2012;Vasanthavigar et al 2010). The concept of water quality to categorize water according to its degree of purity or pollution dated back to 1848 (Vidyalakshmi et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…An SI of zero means water is in equilibrium with the mineral, whereas an SI greater than zero means a supersaturated solution with respect to the mineral in question. Saturation indices indicate whether the water is in equilibrium or not with respect to mineral in question (Chidambaram et al 2011;Singh et al 2012).…”
Section: Hydrogeochemical Analysis For Mineral Phases Using Wateq4fmentioning
confidence: 99%